Imaginary friend: From children's lives to the subjectivity of adults (Research, Society and Development, 2024)
The child's play, in alignment with fantasy, is a resource used as a form of internalization and expression of the external world. Among the imaginative ways, the imaginary friend is found, which symbolizes company, fun, protection, safety, and affection. Considering that few Brazilian studies have been found on the subject, this work aims to study the imaginary friend’s contribution to the construction of the subjectivity of the adult and collaborate for the advancement and expansion of the national studies in the subject. The research was hold by four elementary school teachers from a State School in the city of Patos de Minas-MG, who recalled this experience. For this, we used an oral interview, without recording containing 20 questions and as a complementary and free expression form: a logbook. The results obtained on the imaginary friend, confirm its mediator role that the children use to deal with and to express their psychoemotional thoughts, it is the very particular way of representing children's experiences and endure traumatic episodes that are all over life. Therefore, it is concluded that the subjectivity of the adult is intimately changed by the children's experiences and their creative capacity, and also that the experiences of the stages of development are interdependent from each other, and the benefits of the imaginary friend for adults are multiple; as a sweet and mischievous companion to play with, sharing children's secrets, fulfilling desires and dreams.